Ticks and tick-borne pathogens associated with dromedary camels (Camelus dromedarius) in northern Kenya - Getange, D.; Bargul, J.L.; Kanduma, Esther G.; Collins, M.; Bodha, B.; Denge, D.; Chiuya, T.; Githaka, Naftaly W.; Younan, M.; Fèvre, Eric M.; Bell-Sakyi, L.; Villinger, J. (MDPI, 2021)
Ticks and tick-borne pathogens (TBPs) are major constraints to camel health and production, yet epidemiological data on their diversity and impact on dromedary camels remain limited. We surveyed the diversity of ticks and TBPs associated with camels and co-grazing sheep at 12 sites in Marsabit County, northern Kenya. We screened blood and ticks (858 pools) from 296 camels and 77 sheep for bacterial and protozoan TBPs by high-resolution melting analysis and sequencing of PCR products. Hyalomma (75.7%), Amblyomma (17.6%) and Rhipicephalus (6.7%) spp. ticks were morphologically identified and confirmed by molecular analyses. We detected TBP DNA in 80.1% of blood samples from 296 healthy camels. “Candidatus Anaplasma camelii”, “Candidatus Ehrlichia regneryi” and Coxiella burnetii were detected in both camels and associated ticks, and Ehrlichia chaffeensis, Rickettsia africae, Rickettsia aeschlimannii and Coxiella endosymbionts were detected in camel ticks. We also detected Ehrlichia ruminantium, which is responsible for heartwater disease in ruminants, in Amblyomma ticks infesting camels and sheep and in sheep blood, indicating its endemicity in Marsabit. Our findings also suggest that camels and/or the ticks infesting them are disease reservoirs of zoonotic Q fever (C. burnetii), ehrlichiosis (E. chaffeensis) and rickettsiosis (R. africae), which pose public health threats to pastoralist communities.